2017
DOI: 10.2147/lctt.s140491
|View full text |Cite
|
Sign up to set email alerts
|

Real-world practice patterns for patients with advanced non-small cell lung cancer: multicenter retrospective cohort study in Japan

Abstract: BackgroundRecommended therapies for advanced/metastatic non-small cell lung cancer (NSCLC) have changed with the advent of targeted therapies. The objectives of this retrospective chart review study were to describe treatment patterns, biomarker testing practices, and health care resource use for advanced NSCLC at 5 sites in Japan.Patients and methodsWe studied anonymized medical record data of patients aged ≥18 years who initiated systemic therapy for newly diagnosed stage IIIB or IV NSCLC from January 2011 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
3
18
2
Order By: Relevance
“…However, the population studied in the USA may not be representative of a global population, and additional analyses may be needed to evaluate real-world treatment patterns in other countries. In a retrospective chart review examining real-world practice patterns in 175 Japanese patients treated for stage IIB/IV NSCLC between 2011 and 2013, EGFR TKIs were the most commonly prescribed therapies for EGFR Mut+ NSCLC across all treatment lines [26], similar to our findings. Of note, median OS from the start of first-line therapy was 9.9 months (95% CI 7.6–11.7) for all patients compared with 17.9 months (95% CI 9.9–24.4) for those with EGFR / ALK Mut+ tumors.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, the population studied in the USA may not be representative of a global population, and additional analyses may be needed to evaluate real-world treatment patterns in other countries. In a retrospective chart review examining real-world practice patterns in 175 Japanese patients treated for stage IIB/IV NSCLC between 2011 and 2013, EGFR TKIs were the most commonly prescribed therapies for EGFR Mut+ NSCLC across all treatment lines [26], similar to our findings. Of note, median OS from the start of first-line therapy was 9.9 months (95% CI 7.6–11.7) for all patients compared with 17.9 months (95% CI 9.9–24.4) for those with EGFR / ALK Mut+ tumors.…”
Section: Discussionsupporting
confidence: 79%
“…Of note, median OS from the start of first-line therapy was 9.9 months (95% CI 7.6–11.7) for all patients compared with 17.9 months (95% CI 9.9–24.4) for those with EGFR / ALK Mut+ tumors. The authors note that due to the retrospective nature of the study, these results are not reflective of the current clinical landscape, given the availability of newer therapies for NSCLC, namely third-generation EGFR TKIs [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1440 patients were included in the study from 78 academic and community oncology sites in 8 countries. The demographic and clinical characteristics of all patients have been described by country in previous publications [ 33 , 34 ]. The majority of patients in each country were male (from 53% in Germany to 77% in Spain) and current or former smokers (63% in Korea to 86% in Australia), with the exception of Taiwan (47% male and 33% current or former smokers).…”
Section: Resultsmentioning
confidence: 99%
“…However, platinum-based regimen remains the standard treatment for patients without mutations in China with gemcitabine, docetaxel, paclitaxel and pemetrexed being the most common choices for 1st line chemotherapy (21). A retrospective chart review study examining realworld treatment pattern in Japan revealed EGFR TKIs to be the most commonly prescribed drug for EGFR mutated NSCLC across all treatment lines (22).…”
Section: Discussionmentioning
confidence: 99%